Mentoring English Senior High School Teachers in EFL Reading Class using collaborative Pamanpintermu at SMAM Bungah Gresik - Yudhi Arifani; Harunur Rosyid; Rohmy Husniah; Paulina Paulina (OJS Universitas Muhammadiyah Gresik, 2018)
This community engagement is implemented as result of research dissemination on EFL teaching reading. This paper attempts to assist senior high school teachers in implementing the teaching of reading using collaborative Pamanpintermu reading software in EFL classroom. The mentoring program was conducted for six weeks at SMAM Bungah Gresik. Mentoring and Focus Group Discussion (FGD) is employed for the method of the community engagement. The results of Pamanpintermu implementation in the teaching and learning of EFL reading showed positive response from both teachers and students. Through Pamanpintermu, the teachers could monitor students’ reading progress and they could more effectively address students’ problems in reading class. In the long-term program, it is hoped that Pamanpintermu can be integrated in EFL curriculum at Senior High School in Gresik.